Engineered Circular RNA CircmiR‐29b Attenuates Muscle Atrophy by Sponging MiR‐29b (Adv. Therap. 7/2022). Issue 7 (18th July 2022) - Li, Jin; Chen, Rui; Zheng, Yongjun; Yuan, Weilin; Yang, Tingting; Zhu, Xiaolan; Yan, Yuwei; Jin, Bing; Xu, Wanru; Zhang, Zhongrong; Li, Guoping; Gokulnath, Priyanka; et al.
Abstract : In article 2200029, Junjie Xiao and co‐workers construct an artificial circular RNA named circmiR‐29b as a specific molecular sponge for miR‐29b. The artificial circmiR‐29b treat muscle atrophy by suppressing miR‐29b. As shown in the image, skeletal muscle is a super factory that produce protein and ATP. circmiR‐29b mediate as molecular sponge like the powerful magnets which absorb miR‐29b (arrows) and therefore protect the factory from arrows.